P-EGS04 Assessment of Malnutrition in emergency laparotomy patients. A QIP highlighting simple measures can improve early recognition and optimisation of high-risk patients. (16th December 2021) - Raslan, Charef; Lasheen, Omar; Tomalieh, Feras; Siddique, Khurram
Abstract: Background: Early recognition of high-risk malnourished patients is important for optimisation of nutritional status leading to better outcomes.  The accurate recording of malnutrition universal screening tool (MUST) results is vital in this regard. This quality improvement project (QIP) aimed to review the quality of nutritional assessment of emergency laparotomy patients against the National Institute for Health and Care Excellence (NICE) guidelines and outline area of improvement. Methods: The QIP was conducted at Royal Oldham Hospital in 2019-2020 over a seven-month period.  Fifty random patients were included in the first audit cycle over a 4-month period, followed by implementation of recommended changes and a re-audit of 30 patients over a 2-month period.  The initial MUST scores which were calculated and documented by nursing staff were identified as the nursing staff MUST score (NSMS). To assess the accuracy of NSMS, we developed a MUST rescoring method which was performed by a senior member of the medical team and was identified as the medical team MUST rescore (MTMR).  Results: The initial audit showed a significant difference between NSMS and MTMR scores. According to MTMR, 23 patients (46%) had an inaccurate MUST score assessment by the nursing staff.  A multidisciplinary approach using a standard online calculator were recommended.  The second phase of the QIP showed an obvious improvement in the accuracy of MUST assessment. Our interventions improved the accuracy rate of MUST scores significantly (27, 54% vs 29, 96.6%, P = 0.00005). Conclusions: A multidisciplinary team approach and online calculator are useful in improving the accuracy of MUST assessment in emergency laparotomy patients. This helped early involvement of the dietitian leading to improvement in morbidity and mortality.